Determinasi Literasi Keuangan, Inklusi Keuangan dan Literasi Digital terhadap Kinerja Usaha Mikro Kecil Menengah: Studi pada UMKM di Kabupaten Sumenep - Usmaniyah, Winda; Abrori, Rian (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This research aims to examine the influence of financial literacy, financial inclusion and digital literacy on the performance of micro, small and medium enterprises (MSMEs). This research is quantitative research. The population in this study were all MSMEs in Sumenep Regency using a purposive sampling technique. The sample included in the test criteria was 108 respondents. Test results using multiple linear regression show that financial literacy and digital literacy have an effect on MSME performance, while financial inclusion has no effect on MSME performance. Keyword: financial literacy, financial inclusion, digital literacy, MSMEs